Does Mandating Nondiscrimination in Hiring Practices Influence Women's Employment? Evidence Using Firm-level Data - Amin, Mohammad (World Bank Group, Washington, DC, 2014)
This study explores the relationship between mandating a nondiscrimination clause in hiring practices along gender lines and the employment of women versus men in 58 developing countries. The study finds a strong positive relationship between a nondiscrimination in hiring clause and women's relative to men's employment. The relationship is robust to several controls at the firm and country levels. The results also show sharp heterogeneity in the relationship between the nondiscrimination in hiring clause and women's versus men's employment, with the relationship being much larger in richer countries and in countries with more women in the population as well as among relatively smaller firms.